Arcturina serrulatus sp. nov. and a new record of Limnoria rhombipunctata (Crustacea: Malacostraca: Isopoda) from South Korea - Song, Ji-Hun; Park, Taeseo; Kim, Won; Min, Gi-Sik (Zootaxa, 2017)
A new benthic isopod species, Arcturina serrulatus sp. nov. (Arcturidae Dana, 1849), is described from South Korea. Additionally, we report Limnoria rhombipunctata Yoshino, Watabe & Ohsawa, 2017 (Limnoriidae White, 1850) from the rhizome of Zostera sp. (seagrass). These are the first records of species belonging to the families Arcturidae and Limnoriidae from South Korea. We provide detailed descriptions of the diagnostic characters of the two species. We also determined their partial sequences of the mitochondrial cytochrome c oxidase subunit 1 (CO1) for molecular diagnosis.